Overcoming Constraints in Literary Translation: A Case Study of Rendering Saud Al-Sanousi’s Saq Al-Bambu into English - Rababah Sarah; Al-Abbas Linda (Open Cultural Studies, 2022)
This article aims to investigate the constraints on the English translation of the Arabic novel Saq Al-Bambu (The Bamboo Stalk) and identify the translation strategies that were adopted to render the literary work in light of Baker’s Taxonomy (1992). Examples were collected and classified thematically into four categories: social constraints, political constraints, religious constraints, and cultural constraints. The findings showed that the English translation used general terms to refer to specific concepts in the original novel, and some words were added for explicating purposes. Translation by omission is only used in religious and cultural constraints, which explains the gap between the source language and the target language (TL). The study recommends that translators be aware of the different constraints when rendering a literary work and resort to explanatory notes or footnotes to explain the meaning of items that do not have an equivalent in the TL.